SEG Technical Program Expanded Abstracts 1987 1987
DOI: 10.1190/1.1892016
|View full text |Cite
|
Sign up to set email alerts
|

A method of measuring acoustic wave attenuation in the laboratory

Abstract: The measurement of attenuation is performed by directly determining the attenuation operator (or the impulse response of the medium) in the time domain. In this way, it is possible to separate the attenuation operator from other non-attenuation effects, e.g. reflections. The Wiener filtering technique, or the damped least-squares, is used to calculate the attenuation operator. For the damped least squares, we have corrected for the effect due to the addition of the damping constant using a perturbation method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Their work shows clearly that at short distances from the transmitting transducer, the attenuation values measured in pulse-echo method show wide variation. At long distances however, the results are consistent and it is possible to get an average value of 0.04417 np/cm for the attenuation constant though it is not in agreement with other reported values [3][4][5][6]. Their measurement in through-transmission method uses two transducers aligned face-to-face, parallel to each other.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Their work shows clearly that at short distances from the transmitting transducer, the attenuation values measured in pulse-echo method show wide variation. At long distances however, the results are consistent and it is possible to get an average value of 0.04417 np/cm for the attenuation constant though it is not in agreement with other reported values [3][4][5][6]. Their measurement in through-transmission method uses two transducers aligned face-to-face, parallel to each other.…”
Section: Resultsmentioning
confidence: 71%
“…It is observed that at relatively small distances from the transducer, α varies widely, while at large distances it is possible to obtain an average value of α. Moreover, the values of α obtained from pulse-echo and through transmission methods differ significantly and do not agree with other values reported in the literature [3][4][5][6]. The propagating-wave analysis of pulse-echo method [1] gives a satisfactory explanation for the variation.…”
mentioning
confidence: 79%
“…The spectral ratio method Toks6z et al, 1979;Remi et al, 1994 was used to calculate the frequency dependent attenuation and the low frequency P-wave and s-wave velocity. As the reference standard we chose water with the same length as the samples to avoid geometric spreading effects (Tang et al, 1988). The spectrum UTej of the reference standard has been computed with half a cycle of the first arriving pulse where ATef is the amplitude spectrum, +Tej the phase, w the angular frequency, Kef the phase velocity and Lref the length of the reference standard.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…clay concentration), and these changes have little influence on the acoustic signal energy. At the same time, the elastic wave absorption Q f in the borehole fluid can vary significantly (Cheng, Toksöz and Willis ; Tang, Toksöz and Tarif ). The calculations performed have shown that the amplitudes of the packets of compressional and shear waves depend slightly on the absorption in the borehole fluid (Fig.…”
Section: Dependence Of the Borehole Acoustic Signal Energy On The Acomentioning
confidence: 99%